Innovative Akidah Akhlak Learning Through The Behavioristic-Religious Model (BRM) At MTS Ma’arif NU 2 Cilongok - Evalasefa Muktiyusrina; Donny Khoirul Azis (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study examines the implementation of behavioristic strategies in Akidah Akhlak instruction at MTs Ma’arif NU 2 Cilongok and introduces the Behavioristic–Religious Model (BRM) as its main theoretical contribution. Using a qualitative case study design, data were collected through interviews, observations, and documentation. The findings show clear improvements in students’ moral behavior following consistent application of reinforcement, teacher modeling, and religious habituation. Students demonstrated greater punctuality, increased active participation in learning activities, and a noticeable reduction in discipline violations. Daily religious routines such as congregational prayers, Qur’anic recitation, and structured devotional practices functioned as natural reinforcers that strengthened the internalization of moral values beyond temporary stimulus–response compliance. The novelty of Behavioristic–Religious Model (BRM) lies in its systematic integration of operant conditioning, the law of effect, social modeling, and Islamic school culture into a single framework for character formation. Practically, the model offers teachers and schools a replicable approach to designing learning environments that align pedagogical reinforcement with spiritual habituation to enhance moral behavior in Islamic education.